IMPLEMENTASI NILAI BUDAYA GREBEG BESAR MODEL DISCOVERY LEARNING BERBANTUAN PPt INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA SDN JLEPER 2 - Muhammad David Nifhar; Erik Aditiya Ismaya; Rani setiawaty (Universitas Tribhuwana Tunggadewi, 2024)
This research was conducted in class IV of SD N Jleper 2 Mijen Demak and involved 19 students. This study aims to improve social studies learning outcomes and teachers' ability to teach social studies content by applying the cultural values of Grebeg Besar of Demak Regency through interactive PowerPoint media used by the Discovery learning model. In this study, students' social studies learning outcomes and teachers' teaching skills are the dependent variables. Grebeg Besar cultural values, interactive PowerPoint media, and discovery learning model are independent variables. Observation, interview, test, and documentation are the data collection methods. Quantitative and qualitative data analysis were used. The results of the teacher teaching skills research also increased, at 64% (sufficient) and 82% (good) in cycle I, and 57% (less) in cycle II. Thus, learning outcomes and teacher teaching skills in social studies content can be improved by applying the cultural values of Grebeg Besar of Demak Regency with the help of interactive PowerPoint media and Discovery Learning learning model.